Cryopreservation of Siberian tiger (Panthera tigris altaica) epididymal spermatozoa: pilot study of post-thaw sperm characteristics - Saddah Ibrahim; Nabeel Abdelbagi Hamad Talha; Jeongho Kim; Yubeol Jeon; Iljeoung Yu (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Epididymal sperm cryopreservation provides a potential method for preserving genetic material from males of endangered species. This pilot study was conducted to develop a freezing method for tiger epididymal sperm. We evaluated post-thaw sperm condition using testes with intact epididymides obtained from a Siberian tiger (Panthera tigris altaica) after castration. The epididymis was chopped in Tyrode's albumin-lactate-pyruvate 1x and incubated at 5% CO2, 95% air for 10 min. The Percoll separation density gradient method was used for selective recovery of motile spermatozoa after sperm collection using a cell strainer. The spermatozoa were diluted with modified Norwegian extender supplemented with 20 mM trehalose (extender 1) and subsequent extender 2 (extender 1 with 10% glycerol) and frozen using LN2 vapor. After thawing at 37℃ for 25 s, Isolate® solution was used for more effective recovery of live sperm. Sperm motility (computerized assisted sperm analysis, CASA), viability (SYBR-14 and Propidium Iodide) and acrosome integrity (Pisum sativum agglutinin with FITC) were evaluated. The motility of tiger epididymal spermatozoa was 40.1 ± 2.0%, and progressively motile sperm comprised 32.7 ± 2.3%. Viability was 56.3 ± 1.6% and acrosome integrity was 62.3 ± 4.4%. Cryopreservation of tiger epididymal sperm using a modified Norwegian extender and density gradient method could be effective to obtain functional spermatozoa for future assisted reproductive practices in endangered species.